The scenes about miracles in the Sofia Second Chronicle: Historical and anthropological research - A.L. Novosyolov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2018)
The paper discusses the place and role of the scenes about miracles in the Sofia Second Chronicle. From the historical and anthropological point of view, these episodes are studied as parts of the chronicle text that have certain symbolic values. These values have been interpreted by defining of the relations between of the scenes about miracles and other parts of the text of the Sofia Second Chronicle and the Bible. A close relation between the semantic content of miracles in the chronicle and the historical context of its creation has been shown: the events described are evaluated based on the historical events that took place in the Russian Orthodox Church; the evidence of miracles is used as a proof and set forth accordingly. It has been proved that the description of the scenes about the miraculous healings of Konstantin Dmitrievich and Gregory Tumgan at the relics of Varlaam Khutynsky in the Sofia Second Chronicle can be due to the need for political justification for the annexation of Novgorod by the Grand Principality of Moscow in the 1470s. In addition, it has been suggested that interpreting the symbolic meaning of diseases healed miraculously reveals the general meaning of both the scene of the miracle and prior/subsequent events.